2019
DOI: 10.3390/w11122526
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Man–Made Ponds on Soil Erosion and Sediment Transport in Limnological Basins

Abstract: The impact of ponds on basins has recently started to receive its well-deserved scientific attention. In this study, pond-induced impacts on soil erosion and sediment transport were investigated at the scale of the French Claise basin. In order to determine erosion and sediment transport patterns of the Claise, the Coordination of Information on the Environment (CORINE) erosion and Soil and Water Assessment Tool (SWAT) models were used. The impact of ponds on the studied processes was revealed by means of land… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Landscape-scale conservation of urban wetlands is increasingly recognised as important, but this requires methods for spatial data acquisition and analysis suited to this scale. Limited attempts have been made to quantify pond and lake numbers at regional or national scales (Lacaux et al, 2007;Al Sayah et al, 2019), but high levels of uncertainty are evident, reflecting the spatial resolution of remote sensing data and the associated difficulty of identifying the smallest ponds. Pond numbers have been estimated to be between 547 million and 3.19 billion globally, with the wide range in these values demonstrating the uncertainty surrounding estimates (Holgerson and Raymond, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Landscape-scale conservation of urban wetlands is increasingly recognised as important, but this requires methods for spatial data acquisition and analysis suited to this scale. Limited attempts have been made to quantify pond and lake numbers at regional or national scales (Lacaux et al, 2007;Al Sayah et al, 2019), but high levels of uncertainty are evident, reflecting the spatial resolution of remote sensing data and the associated difficulty of identifying the smallest ponds. Pond numbers have been estimated to be between 547 million and 3.19 billion globally, with the wide range in these values demonstrating the uncertainty surrounding estimates (Holgerson and Raymond, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Globally, pond numbers have been estimated to be between 547 million -3.19 billion globally, demonstrating the uncertainty surrounding pond numbers at national and international scales (Holgerson and Raymond, 2016). Limited attempts have also been made to quantify pond numbers at regional or national scales (Al Sayah et al, 2019;Lacaux et al, 2007), with similar high levels of uncertainty, reflecting the spatial resolution of remote sensing and identification of the smallest ponds.…”
Section: Discussionmentioning
confidence: 99%
“…Xin et al [36] observed simulated rainfall experiments to observe the infiltration processes of black soil slopes under bare and residue-covered situations. A study of the impact of ponds in limnologically rich basins on soil erosion and sediment transport has been reported by Al Sayah et al [37]. The construction of a debris-blocking dam has been studied by Wang et al [38] under various downstream riverbed slope conditions.…”
Section: Literature Reviewmentioning
confidence: 99%